Paleotopography of Glacial-Age Ice Sheets - Edwards, R. Lawrence; Peltier, W. R. (Science (American Association for the Advancement of Science), 1995)
The model of the paleotopography of glacial-age ice sheets suggesting a lower elevation for the northern hemisphere sheet than previously believed should be corrected for tectonic uplift in Papua New Guinea and Barbados.